IMPLEMENTASI PROGRAM PEMBERDAYAAN FAKIR MISKIN MELALUI BANTUAN LANGSUNG PEMBERDAYAAN SOSIAL DI KELURAHAN GUBUKUSUMA KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN - Baharuddin, Ilfan (Aksara Public, 2018)
Abstract This study intends to explore and analyze how the implementation of the Poor Empowerment Program through Direct Social Empowerment in Gubukusuma Village, North Tidore Subdistrict Tidore Kepulauan City as one of the strategic business to increase the family's economic income in the survival, the method used in this study is descriptive qualitative, while the main instrument in the field data collection conducted through in-depth interviews, participatory observation and to obtain additional data traced also written reports from the Head of Kelurahan Gubukusuma, Joint Business Group I Kelurahan gubukusuma and Social Service Work and Transmigration of Tidore Islands The islands are concerned with the research focus. Based on the findings of the field show that: First, the existence of obstacles in the implementation of the program such as information delays by the village, the information is less accurate so that there are differences of interpretation from various target groups and socialization of programs that are less intense and maximized on the program development system. Second, the target group/KUBE I acknowledge that they have a lack of experience and information about agriculture that requires competent companions, but the government (Head of Social Affairs) says that they experience a shortage of personnel resources and monitoring funds making it difficult to provide targeted assistance to the target group. In conclusion, Implementation of Poor Empowerment Program through KUBE of Kelurahan Gubukusuma Sub-district of North Tidore has not got significant result either from quantity or quality of service, either from program development and supervisor / social assistance side.